2013
DOI: 10.4172/2155-9899.s10-007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-NMDA Receptor Encephalitis

Abstract: In recent years, the discovery of antibodies to specific neuronal antigens that then go on to cause encephalitis has gone a long way to change the investigation and management of a potential encephalitic process. These have now become known under the umbrella term of the 'autoimmune encephalitides'. In this article we look at anti-N-methyl-D-aspartate receptor encephalitis, a condition most often found in young females and has an association with a number of malignancies, most commonly ovarian teratomas. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Even in research, experts say that NMDAR antibodies are identified only in 1% of patients aged 18-35 years who are treated in intensive care units. 3,4,6 Anti-NMDAR encephalitis must be distinguished from encephalitis caused by other etiologies because of different clinical manifestations. In anti-NMDA receptor positive encephalitis, there are some symptoms that are rarely seen in viral encephalitis, such as hallucinations, psychosis, personality changes and irritability, although in 70% of cases patients initially have prodromal symptoms similar to viral symptoms such as fatigue, headache, symptoms of upper respiratory tract disorders, nausea, diarrhea, myalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Even in research, experts say that NMDAR antibodies are identified only in 1% of patients aged 18-35 years who are treated in intensive care units. 3,4,6 Anti-NMDAR encephalitis must be distinguished from encephalitis caused by other etiologies because of different clinical manifestations. In anti-NMDA receptor positive encephalitis, there are some symptoms that are rarely seen in viral encephalitis, such as hallucinations, psychosis, personality changes and irritability, although in 70% of cases patients initially have prodromal symptoms similar to viral symptoms such as fatigue, headache, symptoms of upper respiratory tract disorders, nausea, diarrhea, myalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Cabe destacar que el teratoma es la neoplasia más frecuente que se asocia a la encefalitis anti-NMDAR. No obstante se han descrito otras neoplasias, como teratomas mediastinales, tumores estromales, neuroblastomas y linfoma de Hodgkin (5) .…”
Section: Introductionunclassified
“…Phillip Ferdinand and Lauren Mitchell covers the autoimmune encephalitides disorders particularly focussing on anti-N-methyl-D-aspartate receptor encephalitis, one possible cause of which are the antibodies against the NR1 subunit of the receptor. They propose that treatment by induction of immunosuppressive therapy and management of long term residual deficits with the following remission of the autoimmune process could be beneficial [11].…”
mentioning
confidence: 99%